Resorption of lumbar disc herniations: a non-systematic literature review - Abdugafur J. Sanginov; Ilya D. Isakov; Shamil A. Akhmetyanov; Aleksey V. Peleganchuk (Хирургия позвоночника, 2024)
Objective. To analyze the information on spontaneous resorption of lumbar disc herniation. Material and Methods. A non-systematic review of 37 publications on resorption of disc herniation was conducted. The data on the timing, mechanisms and predictors of regression of lumbar disc herniation were summarized. A clinical case is presented illustrating the resorption of a herniated L4–L5 intervertebral disc over 8 months. Results. The frequency and timing of resorption of lumbar disc herniation vary depending on the number of patients, follow-up period, the type and nature of the hernial bulging, and other characteristics of patients. The results of meta-analyses indicate that the average period of spontaneous resorption of lumbar disc herniation is more than 6 months. The main theories of spontaneous resorption of lumbar disc herniation are the dehydration theory, the mechanical theory, and mechanisms associated with inflammatory processes and neovascularization. Currently, predictors of disc herniation resorption include the type and size of the hernia, follow-up period, Modic changes, etc. Existing data on the timing, mechanisms and predictors of resorption of lumbar disc herniation are insufficient to improve treatment tactics for this category of patients. Conclusion. Herniated lumbar intervertebral discs tend to undergo spontaneous regression which, however, is not observed in all patients. The mechanisms of resorption can be different, and the fact of resorption itself can occur in different types of hernia with different frequencies. An analysis of large data sets is necessary to more accurately determine the timing and predictors of resorption of lumbar disc hernias.